Effect of routine probiotic, Lactobacillus reuteri DSM 17938, use on rates of necrotizing enterocolitis in neonates with birthweight < 1000 grams: a sequential analysis - Hunter Chelsea; Dimaguila Mary Ann VT; Gal Peter; Wimmer John E; Ransom James; Carlos Rita Q; Smith McCrae; Davanzo Christie C (BMC, 2012)
Abstract Background Necrotizing enterocolitis (NEC) is a disease in neonates, often resulting in death or serious medical or neurodevelopmental complications. The rate of NEC is highest in the smallest babies and many efforts have been tried to reduce the rate of NEC. In neonates born below 1500 grams, the rate of NEC has been significantly reduced with the use of various probiotics. This study examines the impact of routine use of a probiotic, Lactobacillus reuteri DSM 17938 (BioGaia®), on the rate of NEC in neonates at highest risk for developing NEC, those with birth weight ≤1000 grams. Methods This is a retrospective cohort study comparing the rates of NEC in neonates with birth weight ≤ 1000 grams. The groups are separated into those neonates born from January 2004 to June 30, 2009, before introduction of L. reuteri , and neonates born July 2009 through April 2011 who received routine L. reuteri prophylaxis. The chart review study was approved by our institutional review board and exempted from informed consent. Neonates were excluded if they died or were transferred within the first week of life. The remainder were categorized as having no NEC, medical NEC, surgical NEC, or NEC associated death. Since no major changes occurred in our NICU practice in recent years, and the introduction of L. reuteri as routine prophylaxis was abrupt, we attributed the post-probiotic changes to the introduction of this new therapy. Rates of NEC were compared using Chi square analysis with Fisher exact t-test. Results Medical records for 311 neonates were reviewed, 232 before- and 79 after-introduction of L. reuteri prophylaxis. The incidence of NEC was significantly lower in the neonates who received L. reuteri (2 of 79 neonates [2.5%] versus 35 of 232 untreated neonates [15.1%]). Rates of late-onset gram-negative or fungal infections (22.8 versus 31%) were not statistically different between treated and untreated groups. No adverse events related to use of L reuteri were noted. Conclusions Prophylactic initiation of L. reuteri as a probiotic for prevention of necrotizing enterocolitis resulted in a statistically significant benefit, with avoidance of 1 NEC case for every 8 patients given prophylaxis.